Identification Of Factors Influencing Customer’s Continuance Inten-tion In The Post-Adoption Phase Of A Cloud-Based Human Resource Management System - Alfatianisa, Kirana; Hidayanto, Achmad Nizar (Syntax Corporation, 2026)
The advancements in information technology during the digital transformation era have encouraged organizations to adopt cloud-based systems to improve their operational efficiency, including in human resource management area. Human Resource Management Systems (HRMS) have become a critical component in enabling integrated automation of HR processes. PT XYZ, as a vendor providing cloud-based HRMS through its product HRTechIndo, has supported the digitalization of HR processes for various organizations in a Business-to-Business (B2B) setting. However, the stagnant customer retention rate that has always been below the target indicates system utilization that is not optimal. This condition requires attention, because low retention may hinder PT XYZ’s business sustainability, which relies on loyalty and long-term relationships with clients. This study aims to identify the factors influencing continuance intention in PT XYZ. The research model was developed by integrating the Expectation Confirmation Model (ECM) and the Technology-Organization-Environment (TOE) framework. PLS-SEM was employed to analyze data from 184 respondents representing 36 client organizations, supported by literature review and qualitative validation through interviews. The results show that confirmation, perceived usefulness, satisfaction, vendor service quality, and organizational fit significantly influence continuance intention. Meanwhile, cloud system quality indirectly affects continuance intention through satisfaction, and perceived value does not influence it significantly. These findings highlight that the continuance intention of HRTechIndo’s usage by clients is primarily driven by perceived benefits, post-adoption experience, vendor service quality, and alignment between the system and organizational processes.